Jørgen Leth - Film Portraits, Disc 1 - Leth, Jorgen; Holmberg, Dan; Weincke, Jan; Salomon, Mikael; Klitgaard, Peter (Danish Film Institute, 2008)
In "Peter Martins: A Dancer" (1978), Martins, at the apex of his career as lead dancer and choreographer at the New York City Ballet, talks about his intellectual and physical journey from the Bournonville tradition to Balanchine's lab. Leth is equally consumed with investigating how choreography takes shape. How do dancers and director communicate? In "Dancing Bournonville" (1979), Leth follows the Royal Danish Ballet's solo dancers as they rehearse The Kermesse in Bruges (The Three Gifts) and other dances. One sequence illustrates Bournonville's notion of the combined ballet moves and mimic expression, as Bournonville expert Hans Brenaa instructs ballerina Mette Ida Kirk. In "Step on Silence" (1981), Leth returns to the footage from his Peter Martins film, and in collaboration with Kristian Levring, re-edits the footage, showing multiple takes of the same detail in succession to illustrate the laborious and often exhausting process that takes place in the rehearsal studio. [www.dfi.dk]
Keywords: DVD-Video